O współczesnych orientacjach w teorii i praktyce zarządzania przedsiębiorstwami / - Lichtarski, Jan (On Contemporary Orientations in Management of the Company, 2008)
This paper defines the issue of the orientation in management. Theoretical and practical premisses which indicate the necessity of describing, analizing and explaining of them have been presented as well. In the next part of the paper such types of these kind of premisses are distinguished and divided into: market orientation, qualitative orienatation, orientation focused on results, strategic orientation, change orientation, process orientation and orientation focused on knowledge. In the final conclusions, the author presents the basic recommendations and challenges connected with the implementation of these orientations. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 51-57